Multiple Stereoelectroencephalography-Guided Radiofrequency Thermocoagulations for Polymicrogyria With Startle Seizures: A Case Report - Liu, Yi'Ou; Zhou, Wenjing; Hong, Bo; Zhao, Tong; Xu, Chengwei; Ruan, Jing; Bai, Jianjun; Wang, Siyu (Frontiers in Neurology, 2019)
ABSTRACT: The best results of SEEG-guided radiofrequency thermocoagulation (SEEG-guided RF-TC) were observed in epilepsies with more limited lesions, and it was rarely used in wide-range brain malformation.We report a rare case of polymicrogyria (PMG) combined with drug-resistant startle seizures，pre-surgical monitoring was performed using stereoelectroencephalography (SEEG) due to the large lesion and complexity of PMG. According to the intracranial electrode results, the seizure onset were extensive, with the cingulate sulcus and insular pole starting earlier than the sites of the other electrodes. Multi-point and multi-step SEEG-guided RF-TC was used for diffuse lesion and functional protection . RF-TC was first applied to the cingulate sulcus and insular pole , and the patient was rendered free of startle seizures after 2 weeks , 2 weeks of observation helped us to observe the efficacy of RF-TC and the changes of SEEG ，so as to make the next thermocoagulation scheme. Patient still had spontaneous seizures after first treatment,RF-TC was then applied to other sites involved earlier. Finally, the patient reached Engel class IIa for a follow-up period of one year. There were no additional startle seizures, and important functional areas were protected. Keywords: Multiple SEEG-guided RF-TC, polymicrogyria, startle seizure , stereoelectroencephalography (SEEG), surgical outcome